2020
DOI: 10.1155/2020/9235638
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in the Treatment of Metastatic Melanoma: Current Knowledge and Future Directions

Abstract: Melanoma is one of the most immunologic malignancies based on its higher prevalence in immune-compromised patients, the evidence of brisk lymphocytic infiltrates in both primary tumors and metastases, the documented recognition of melanoma antigens by tumor-infiltrating T lymphocytes and, most important, evidence that melanoma responds to immunotherapy. The use of immunotherapy in the treatment of metastatic melanoma is a relatively late discovery for this malignancy. Recent studies have shown a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
160
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 161 publications
(225 reference statements)
0
160
0
11
Order By: Relevance
“…Several chemotherapeutic drugs, including dacarbazine, cisplatin, trosulfan, temozolomide and fotemustine, have been investigated, exhibiting a low response rate and disappointing outcomes ( 114 , 147 ). While immunotherapy has noticeably improved outcomes in metastatic cutaneous melanoma, this has not been the case for metastatic UM ( 148 ). A possible reason for such a different response to immunotherapy could be related to the different biological characteristics between cutaneous and UMs, as well as their different immunogenicity ( 149 , 150 ).…”
Section: Surveillance and Metastatic Disease Treatmentmentioning
confidence: 99%
“…Several chemotherapeutic drugs, including dacarbazine, cisplatin, trosulfan, temozolomide and fotemustine, have been investigated, exhibiting a low response rate and disappointing outcomes ( 114 , 147 ). While immunotherapy has noticeably improved outcomes in metastatic cutaneous melanoma, this has not been the case for metastatic UM ( 148 ). A possible reason for such a different response to immunotherapy could be related to the different biological characteristics between cutaneous and UMs, as well as their different immunogenicity ( 149 , 150 ).…”
Section: Surveillance and Metastatic Disease Treatmentmentioning
confidence: 99%
“…Recently, a randomized placebo-controlled study in stage III patients with CM demonstrated that adjuvant ipilimumab increases relapse-free survival (RFS) and OS. Nevertheless, more than half of patients developed severe side effects (grade 3 or 4) with ipilimumab, and five patients (1.1%) even had a grade 5 outcome [ 23 , 24 , 25 , 26 , 27 ]. As a result of ipilimumab-induced T cell activation, a variety of immune-mediated adverse effects (irAEs) have been observed, particularly including colitis, skin rashes, hepatitis, and less frequently hypophysitis.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Two studies demonstrated that the combination of nivolumab plus ipilimumab (ORR: 56.7%) resulted in higher clinical benefit when compared to -nivolumab (ORR: 43.7%) or mono-ipilimumab (ORR: 19%). Five-year OS rates were 52% in the combined treatment arm, 44% in the mono-nivolumab arm, and 26% in the mono-ipilimumab arm [ 26 , 27 , 28 , 29 ]. In 2015, the combination of nivolumab plus ipilimumab was approved based on positive ORR and PFS data.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Next, we evaluated the immunological repercussions for cell death within melanoma cells following Ru PDT. 2 Considering the positive correlation between antitumor immunity and better melanoma outcomes, 3,4 we specifically investigated a phenomenon of immunogenic cell death (ICD) within Ru PDT-treated melanoma cells. In the context of cancers, ICD is a regulated form of cell death that encompasses a cascade of immune responses 5,6 promoting adjuvanticity and antigenicity -both essential for the development of antitumor immunity.…”
Section: Photosensitizer; Photodynamic Therapy; Immunogenic Cell Deatmentioning
confidence: 99%